2008
DOI: 10.1038/jid.2008.39
|View full text |Cite
|
Sign up to set email alerts
|

Akt Blockade Downregulates Collagen and Upregulates MMP1 in Human Dermal Fibroblasts

Abstract: Acutely transforming retrovirus AKT8 in rodent T-cell lymphoma (Akt) is a serine/threonine kinase that plays important roles in survival, cell-cycle progression, and cell proliferation, and has recently been implicated in collagen regulation. The aim of this study was to determine the role of Akt in collagen deposition by normal dermal fibroblasts, and to determine the sensitivity of cultured systemic sclerosis (SSc) fibroblasts to Akt inhibition. We show that blockade of Akt using pharmacological inhibitors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 62 publications
5
73
0
Order By: Relevance
“…4a and b). TGF-ß1 decreased the mRNA levels of MMP1a and MMP1b, similarly to that in the study of Bujor et al (106) in human dermal fibroblasts, but IL-4 had no effect ( Fig. 4c and d).…”
Section: Discussionsupporting
confidence: 71%
“…4a and b). TGF-ß1 decreased the mRNA levels of MMP1a and MMP1b, similarly to that in the study of Bujor et al (106) in human dermal fibroblasts, but IL-4 had no effect ( Fig. 4c and d).…”
Section: Discussionsupporting
confidence: 71%
“…As well as in keloids, epigenetic modification of the promoters of DKK1 and SFRP1 seems to contribute to aberrant Wnt signaling in SSc (43). Finally, the AKT pathway has been reported to promote fibrosis because inhibition of this pathway can reduce collagen production by human fibroblasts (26,27). A decrease in dermal thickness, collagen content, and a-SMA in the skin of niclosamide-treated HOCl-mice corroborates the role of STAT3, AKT, and Wnt/b-catenin pathways in skin fibrosis in this model and emphasizes the therapeutic potential of coinhibitors of these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This signaling pathway is involved in patients with SSc because it is overexpressed in human skin where it activates fibroblasts and promotes their differentiation into myofibroblasts (24,25). Furthermore, the AKT signaling pathway seems to be implicated in fibrosis because its inhibition can reduce collagen production by human fibroblasts (26,27). Moreover, this pathway can affect b-catenin by inhibiting GSK3b and stabilizing b-catenin (28,29).…”
mentioning
confidence: 99%
“…One additional mechanism involving the c-Abl kinase has been implicated in the development of fibrosis in SSc. This study focused on the activation of Smad1 in SSc and found that that levels of phosphorylated Smad1 were [56]. Furthermore, Akt/PKB may participate in EMT induction through phosphorylation of GSK-3 and also increase cell proliferation and survival through its inhibition of apoptotic pathways.…”
Section: Growth Factorsmentioning
confidence: 99%